2008
DOI: 10.2319/022707-102.1
|View full text |Cite
|
Sign up to set email alerts
|

Rebonding of Orthodontic Brackets

Abstract: The results confirm the original hypothesis that differences in adhesive systems are manifested in less aggressive etches and less adhesive left on the enamel surface for the self-etching adhesive systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…For ARI to the Concise TM orthodontic (G1) and Transbond TM XT (G3) resins, the results reinforce the research of Derech et al, 5 Montasser et al, 12 and Penido et al 4 who also obtained low scores. On the other hand, our results confront studies which reported the majority of disruptions in the interface composite/ bracket.…”
Section: Resultssupporting
confidence: 81%
“…For ARI to the Concise TM orthodontic (G1) and Transbond TM XT (G3) resins, the results reinforce the research of Derech et al, 5 Montasser et al, 12 and Penido et al 4 who also obtained low scores. On the other hand, our results confront studies which reported the majority of disruptions in the interface composite/ bracket.…”
Section: Resultssupporting
confidence: 81%
“…Inferior behavior was observed for Groups G5E and G5D, in which the self-etching adhesive system was used, and which removes a micrometric layer of dental surface [31][32][33]. Greater unobstruction of enamel and dentinal tubule prisms was verified with the phosphoric acid etching process, [34] as was used in the other experimental groups, allowing better flow of the hydrophobic monomer, with more voluminous and deeper tag formation [32][33][34].…”
Section: Discussionmentioning
confidence: 92%
“…This could be attributed to the resistance effect that the outer enamel layer acquires from the fluoride content of the Clinpro which may be of significant effect especially when using self-etching primers in bonding due to their more superficial etching effect compared with the etching of the conventionally used phosphoric acid. Previous studies [28-30] with scanning electron microscope (SEM) indicated that although self-etch priming agents have the potential to etch the enamel surface, the etching pattern is less deep compared to the etching pattern of phosphoric acid. A chemical bonding capacity through the interaction between some functional monomers and the calcium of residual hydroxyapatite may contribute favorably to the bonding effectiveness [31-33], but fluoride affects the enamel surface rendering it more resistant to demineralization.…”
Section: Discussionmentioning
confidence: 99%